2022
DOI: 10.1038/s41380-022-01624-5
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol use disorder is associated with DNA methylation-based shortening of telomere length and regulated by TESPA1: implications for aging

Abstract: Chronic heavy alcohol consumption is associated with increased mortality and morbidity and often leads to premature aging; however, the mechanisms of alcohol-associated cellular aging are not well understood. In this study, we used DNA methylation derived telomere length (DNAmTL) as a novel approach to investigate the role of alcohol use on the aging process. DNAmTL was estimated by 140 cytosine phosphate guanines (CpG) sites in 372 individuals with alcohol use disorder (AUD) and 243 healthy controls (HC) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 77 publications
3
14
0
Order By: Relevance
“…However, recent studies report that alcohol-associated aging could be related to triggering neuroimmune responses, including pro-inflammatory cytokine release (107) which could affect telomere length. This was shown recently by Jung et al who reported that DNA methylation derived telomere length was 0.06 kilobases shorter per year in patients with alcohol use disorder compared to healthy controls after correcting for BMI and smoking status (p = 0.002) (108). The current study brings new insight by linking brain aging to cognitive performance which is critical for functionality and overall quality of life.…”
Section: Direct Correlation Between Average Daily Alcohol Consumption...supporting
confidence: 73%
See 1 more Smart Citation
“…However, recent studies report that alcohol-associated aging could be related to triggering neuroimmune responses, including pro-inflammatory cytokine release (107) which could affect telomere length. This was shown recently by Jung et al who reported that DNA methylation derived telomere length was 0.06 kilobases shorter per year in patients with alcohol use disorder compared to healthy controls after correcting for BMI and smoking status (p = 0.002) (108). The current study brings new insight by linking brain aging to cognitive performance which is critical for functionality and overall quality of life.…”
Section: Direct Correlation Between Average Daily Alcohol Consumption...supporting
confidence: 73%
“…This was shown recently by Jung et al. who reported that DNA methylation derived telomere length was 0.06 kilobases shorter per year in patients with alcohol use disorder compared to healthy controls after correcting for BMI and smoking status (p = 0.002) ( 108 ). The current study brings new insight by linking brain aging to cognitive performance which is critical for functionality and overall quality of life.…”
Section: Discussionsupporting
confidence: 54%
“…Similar to previous studies, telomere length was significantly shorter in alcohol use disorder patients than in healthy control subjects in this study 9 , 16 . Focusing on the factors that shorten telomeres, it has been reported that AUD patients with liver damage and higher γ-glutamyl transpeptidase (γ-GTP) and aspartate aminotransferase (AST) have shorter telomere lengths 17 , 18 . Thus, the direct effect of alcohol consumption on telomere length has been evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…TESPA1 is involved in the Ca 2+ transfer and genetic variation in TESPA1 might influence the aging process. Mounting evidence has shown that the accumulation of mitochondrial Ca 2+ is significantly related to neuronal apoptosis and other pathways, and enhanced neuronal apoptosis can lead to the neurodegeneration in AD 67 , 68 .…”
Section: Discussionmentioning
confidence: 99%